A gastrin releasing peptide from the porcine nonantral gastric tissue. Issue 9 (September 1978) - McDonald, T J; Nilsson, G; Vagne, M; Ghatei, M; Bloom, S R; Mutt, V
Abstract : This paper presents evidence for the existence in extracts from porcine non-antral gastric tissue of a peptide capable of causing substantial rises of plasma immunoreactive gastrin levels in a dose dependent manner and of stimulation of gastric acid and pepsin secretion. Obtained data show that the peptide is basic and that its gastrin releasing properties are at least partially resistant to atropinisation and beta-receptor blockade. Antrectomy almost eliminates the rise in plasma IRGa when the peptide is administered. The possible relationship of this peptide to amphibian bombesin is discussed.